Keeping safety in ozone therapy in the dental clinic - Judit Martínez Abreu; Mark Weisser (Editorial Ciencias Médicas, 2014)
Ozone is an element of great oxidative power that has shon its therapeutic properties, but it is potentially toxic. To identify the parameters to guarantee safety during the treatment with ozone in the dental clinic. A research study was performed in two phases: firstly, literature review of 38 scientific publications in Hinari, Cochrane, Pubmed, Scopus, Scielo, Dynamed, EBSCOH databases through Infomed net(2005-2012) in which 27 papers were selected. Secondly, theoretical methods of analysis and synthesis as well as induction and deduction were applied, taking into account the accumulated experience by authors after more than 15 years of using ozone therapy in dental clinic, in order to find out the necessary criteria on safety of subjects. For the purpose of guaranteeing safety in ozone therapy for dental use, it is necessary to have informed consent of patient, to observe weather conditions to schedule consultation at the most suitable time, to avail of an ozone concentration equipment, to keep saliva ejector or other disposal method, to comply with the ozone equipment standards set by the manufacturer, to stop giving treatment if there is any adverse reaction to ozone and to register any event in the medical history, and to develop controlled clinical and randomized assay protocols on this topic and to publish the final results. Ozone is safe provided that it is used according to the established norms and appropriate therapeutic dose. Some parameters were identified to keep in mind for the ozone therapy in dental clinic. More clinical assays are required to justify the role of the dental ozone therapy, through evidence-based odontology   Keywords: ozone, dental clinic, toxicity, safety.